Exploring environmental entrepreneurship: identity coupling, venture goals, and stakeholder incentives - York, Jeffrey G.; O'Neil, Isobel; Sarasvathy, Saras D. (Wiley, 2016)
On the basis of a qualitative study of 25 renewable energy ﬁrms, we theorize why and how individuals engage in environmental entrepreneurship, inductively deﬁned as: the use of both commercial and ecological logics to address environmental degradation through the creation of ﬁnancially proﬁtable organizations, products, services, and markets. Our ﬁndings suggest that environmental entrepreneurs: (1) are motivated by identities based in both commercial and ecological logics,(2) prioritize commercial and/or ecological venture goals dependent on the strength and priority of coupling between these two identity types, and (3) approach stakeholders in a broadly inclusive, exclusive, or co-created manner based on identity coupling and goals. These ﬁndings contribute to literature streams on hybrid organizing, entrepreneurial identity, and entrepreneurship’s potential for resolving environmental degradation.